Faktor-Faktor yang Mempengaruhi Prokrastinasi Akademik Mahasiswa (Dewasa Awal) : Tinjauan Sistematik - Ilbasit Taqiyah; Dalila Zati Amani (Intellektika : Jurnal Ilmiah Mahasiswa, 2025)
Academic procrastination is a common phenomenon among students, especially in the early adulthood stage, which can have a negative impact on academic performance and psychological well-being. This research aims to conduct a systematic review of the factors that influence academic procrastination in students in the early adulthood stage. This review includes an analysis of various empirical studies published over a certain period of time, with a focus on identifying factors that contribute to procrastination behavior. The results of the review show that there are two factors that greatly influence academic procrastination, namely self-efficacy and time management.